Ritratto di uno stereotipo? - Portrait of a Stereotype? - Claudia Gandini, CG (Ciceroniana On Line)
The paper examines how Giovanni Pascoli portrays Cicero as both poet and critic in his school-room anthologies Lyra and Epos, published between the end of the 19th and the beginning of the 20th centuries. In the foreword to both textbooks, Cicero emerges as an accomplished orator but a poor poet, a versifier who clings to tradition and whose verses show little sensitivity to the innovations of the so called Neoterics. The paper argues that Pascoli’s opinion is to be understood within the context of the ongoing debate in Italy about approaches to classical studies. Such debate took shape in opposition to the stance taken by German scholars of the Altertumswissenschaft, in particular by Theodor Mommsen who, in his Römische Geschichte, harshly criticises Cicero’s political and literary career. As part of the analysis, the paper studies the criteria underpinning Pascoli’s edition, translation and commentary of epichistorical fragments collected in Epos, with a focus on excerpts from De consulato suo (fr. II S = 10 Court).